Analisis Faktor-Faktor Yang Mempengaruhi Kinerja Keuangan Pada Pemerintah Daerah Kabupaten/Kota Se-Sumatera Tahun 2015-2018 - Dian Sukma; Annie Mustika Putri; Muhammad Ahyaruddin (Jurnal IAKP: Jurnal Inovasi Akuntansi Keuangan & Perpajakan, 2021)
AbstractThe purpose of this study is to analyze the effect of capital spending, size of local government, intergovernmental revenue, and local revenue on regional financial performance. The population in this study were 8 provinces on the island of Sumatera. The sample of this research is 127 regencies / cities. The sampling method in this research is purposive sampling. The data used in this study is secondary data, which is done using documentary techniques. The processing method used is multiple linear regression. Based on the research results, it can be concluded that the variables of capital expenditure, size of local government, intergovernmental revenue, local revenue have an effect on financial performance.Â Keywords: Capital Expenditure; Intergovenrmental Revenue; Financial Performance